Synthesis of nanostructured films of zinc oxide and a study of its structural and luminescent properties - Ilyassov, B.R.; Ibrayev, N.Kh. (IOP Conf. Series: Materials Science and Engineering, 2016)
ZnO nanorod array were synthesized on sol-gel prepared ZnO seed layer over quarts substrates by hydrothermal method. X-ray diffraction results show that nanorods are the typical hexagonal wurtzite structure without any other new phase and preferentially oriented along the c-axis perpendicular to the substrate surface. The scanning electron microscopy (SEM) of the surface of the ZnO film showed vertical ZnO nanorods with hexagonal crossection. The luminescence spectrum of ZnO nanorod array consisted of a narrow UV band and a broad band in visible region of spectrum and its temporal characteristics were measured.
Keywords: Synthesis; nanostructured films; zinc oxide; a study; its structural; luminescent properties